Hybrid multilayer mobility management with AAA context transfer capabilities for all-IP networks. - Politis, C. (IEEE Wireless communications)
This article presents a multilayer mobility management scheme for all-IP networks where local mobility movements (micro-mobility) are handled separately from global movements (macro-mobility). Furthermore, a hybrid scheme is proposed to handle macro-mobility (mobile IP for non-real-time services and SIP for real-time services). The internetworking between micromobility and macro-mobility is implemented at an entity called the enhanced mobility gateway. Both qualitative and quantitative results have demonstrated that the performance of the proposed mobility management is better than existing schemes. Furthermore, a context transfer solution for AAA is proposed to enhance the multilayer mobility management scheme by avoiding the additional delay introduced by AAA security procedures.